138k views
4 votes
1. Change each of the following equations to the form

y = mx + c. Then, state the values of m and c.
(a) -6x- y = 3
(b) 3x - 4y = 12
(c)-2x + 5y = 10
(d) x + 2y = 4
(e) 8x- 4y = 3
(1) 4x + 5y = -6​

1 Answer

6 votes

Answer:

(a) -6x- y = 3


6x + y = -3\\ y = -6x -3

(b) 3x-4y =12


3x - 4y = 12\\-4y = -3x +12\\4y = 3x -12\\\\y = (3)/(4)x -3

(c)-2x + 5y = 10


-2x + 5y = 10\\5y = 2x + 10\\y = (2)/(5)x + 2

(d) x + 2y = 4


x+2y=4\\2y = -x + 4\\y = (-1)/(2) x +2

(e) 8x- 4y = 3


8x - 4y =3\\-4y = -8x + 3\\4y = 8x -3\\y = 2x -(3)/(4)

(f) 4x + 5y = -6


4x + 5y = -6\\5y = -4x - 6\\y = (-4)/(5) x -(6)/(5)

User Mike Jeffrey
by
4.8k points